2020
DOI: 10.1016/j.fertnstert.2019.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endometrial thickness on ectopic pregnancy in frozen embryo transfer cycles: an analysis including 17,244 pregnancy cycles

Abstract: Objective: To investigate whether endometrial thickness (EMT) influences the incidence of ectopic pregnancy (EP) in frozen embryo transfer (FET) cycles. Design: Retrospective cohort study. Setting: Academic tertiary-care medical center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
51
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 53 publications
11
51
2
Order By: Relevance
“…In AC-FET cycles, EMT was recorded from the last ultrasound scan before starting P administration. The maximum distance between two outer edges in the endometrial image of a longitudinal section of the uterus observed by vaginal ultrasound was used to measure (12).…”
Section: Observational Indicators and Main Cycle Outcomesmentioning
confidence: 99%
“…In AC-FET cycles, EMT was recorded from the last ultrasound scan before starting P administration. The maximum distance between two outer edges in the endometrial image of a longitudinal section of the uterus observed by vaginal ultrasound was used to measure (12).…”
Section: Observational Indicators and Main Cycle Outcomesmentioning
confidence: 99%
“…In recent years, ultrasonic parameters, molecular markers in endometrial tissue and uterine secretions, endometrial microstructure, and hysteroscopy have been applied to evaluate endometrial receptivity ( 8 ). The preferred method for assessing endometrial receptivity is transvaginal ultrasound, and multiple ultrasonic indicators have been used to assess endometrial receptivity ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…At present, ultrasonic imaging and expression of related biochemical markers in endometrium have been used to assess endometrial receptivity [5]. Transvaginal ultrasound is the first-line method to observe follicular development and endometrial growth because of its noninvasive characteristics, and ultrasonic parameters, including endometrial thickness, classification and blood flow, have been confirmed to reflect endometrial receptivity [6,7]. This study aimed to assess ovarian reserve function, follicular development and endometrial receptivity in older women and to evaluate the predictive value for endometrial receptivity of different ultrasonic parameters during the implantation window.…”
Section: Introductionmentioning
confidence: 99%